A rare case of bilateral luxatio erecta with bilateral greater tuberosity fracture following a fall due to seizure - Reddy, Siva V. (J Clin Orthop Trauma, 2019)
Luxatio erecta is the least common form of shoulder dislocations. Bilateral luxatio erecta with concomitant greater tuberosity fracture is further rare with only couple of cases reported so far in the literature. We present an uncommon and a rare case of post epileptic seizure related bilateral luxatio erecta with greater tuberosity fracture in a young Indian male which is unique in its etiology, method of management and rarity of its type among so far reported cases.